Analisis Kinerja Angkutan Umum Di Terminal Larangan, Sidoarjo - hammam rofiqi agustapraja (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2021)
Larangan Terminal of Sidoarjo is a class B terminal if based on Permenhub No. 132 of 2015, namely a terminal that stops various public transportation such as AKDP Buses (Inter-Cities In The Province Bus), MPU (car for public transportation), Minibus/Elf that serves inter-city in one province, the total number of public vehicles operating in the terminal is 252 units, with various types of modes and travel routes, this study has a problem formulation of how the performance of public transport operating in the Larangan Terminal of Sidoarjo ? which has the purpose of knowing the performance of public transportation so that later it can become a reference in improving the quality of public transportation services. The method used is a survey method which is divided into two namely static survey and dynamic survey on observations of rush hour and regular hours. The results of the analysis by referring to the standard of public transport services of the Directorate General of Land Transportation Number SK: SK.687 / AJ.206 / DRJD / 2002, that the performance of public transport in the Larangan Terminal of Sidoarjo with existing types of public transport includes AKDP Buses, Elf Minibus, and several types MPU is good, so it needs to be maintained specially to be improved, especially for MPUs that loaded and dropped passengers outside the Terminal, this evaluation needs to improve the services of the Larangan Terminal of Sidoarjo.